Association of Maternal Diabetes Mellitus and Polymorphisms of the NKX2.5 Gene in Children with Congenital Heart Disease: A Single Centre-Based Case-Control Study - Mingyi Zhao; Jingyi Diao; Peng Huang; Jinqi Li; Yihuan Li; Yang Yang; Liu Luo; Senmao Zhang; Letao Chen; Tingting Wang; Ping Zhu; Jiabi Qin (Journal of Diabetes Research)
Background. Congenital heart disease (CHD) is one of the most common birth defects among newborns, accounting for a large proportion of infant mortality worldwide. However, the mechanisms remain largely undefinable. This study aimed to investigate the association of CHD in offspring of mothers with diabetes mellitus (DM) and single nucleotide polymorphisms (SNPs) of NKX2.5. Methods and Results. A case-control study of 620 mothers of CHD patients and 620 mothers of healthy children admitted to Hunan Children’s Hospital from November 2017 to December 2019 was conducted. We collected the mothers’ information by questionnaire and detected children’s NKX2.5 variants with a MassARRAY system. The interaction coefficient (γ) was used to quantify the estimated gene-environment interactions. Univariate and multivariate analyses both showed that the infants had a higher risk of CHD if their mothers had a history of DM, including gestational DM (GDM) during this pregnancy (adjusted odds ratio [aOR=4.98]), GDM in previous pregnancies (aOR=4.30), and pregestational DM (PGDM) in the 3 months before this pregnancy (aOR=6.78). Polymorphisms of the NKX2.5 gene at rs11802669 (C/C vs. T/T: aOR=4.97; C/T vs. T/T: aOR=2.15) and rs2277923 (T/T vs. C/C, aOR=1.74; T/C vs. C/C, aOR=1.61) were significantly associated with the risk of CHD in offspring. In addition, significant interactions between maternal DM and NKX2.5 genetic variants at rs11802669 (aOR=8.12) and rs2277923 (aOR=17.72) affecting the development of CHD were found. Conclusions. These results suggest that maternal DM, NKX2.5 genetic variants, and their interactions are significantly associated with the risk of CHD in offspring.